Implementation of Legal Protection of Children from Violence through Child Protection Institutions in North Sumatra - Atika Sandra Dewi; Asmuni Asmuni; Budi Sastra Panjaitan (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
This research is a legal research related to the implementation of the North Sumatra Child Protection Agency (LPA) in preventing violence against children in North Sumatra Province. This research was conducted using a qualitative research model (mode of inquiry) and included as field research (empirical). This research uses a statutory approach, case approach, normative approach, and conceptual approach. The results of the study found that the role of the North Sumatra Child Protection Agency (LPA) towards children as victims of violence in North Sumatra is currently running well, it's just not optimal and still has obstacles both from internal and external. LPA Provisnsi currently gave birth to the Sekampung Child Protection Movement Program (GPAS), as a strategy to protect children's growth and development and prevent delinquency and child abuse from an early age. To the government, it should reconstruct the legal protection of children based on prosperity, through; First, Law Number 11 of 2012 concerning the Child Criminal Justice System Article 55, paragraph (3); related to scheduling children's trials, and Second, Law Number 35 of 2014 concerning Child Protection, Article 88: related to punishment